1974
DOI: 10.1002/food.19740180204
|View full text |Cite
|
Sign up to set email alerts
|

Darstellung und sensorische Eigenschaften von alkylsubstituierten 2‐Hydroxy‐buten(2)‐oliden(1,4) und strukturverwandten Verbindungen

Abstract: Unter Nutzung verschiedener Synthesewege sind sieben 2‐Hydroxy‐buten‐(2)‐olide(1,4) sowie weitere vier strukturverwandte Verbindungen dargestellt worden, davon insgesamt sieben Verbindungen erstmalig. Als günstiges Darstellungsverfahren erwies sich die Umsetzung von 2‐Oxo‐buttersäure mit Aldehyden in Gegenwart von konzentrierter Schwefelsäure. Geruchseigenschaften und Geruchsschwellenwerte der dargestellten Substanzen werden wiedergegeben und diskutiert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…and of their potential use as antimicrobial5 and flavouring agents. 6 The parent 3-methoxy-2(5H)-furanone (1) has been isolated from natural sources. ' We report here our results on the mass spectral fragmentation mechanisms of a series of isotetronic acid methyl ethers (shown below) supported by labelling studies, high resolution data and metastable ion peak measurements.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and of their potential use as antimicrobial5 and flavouring agents. 6 The parent 3-methoxy-2(5H)-furanone (1) has been isolated from natural sources. ' We report here our results on the mass spectral fragmentation mechanisms of a series of isotetronic acid methyl ethers (shown below) supported by labelling studies, high resolution data and metastable ion peak measurements.…”
Section: Resultsmentioning
confidence: 99%
“…High resolution mass spectra were measured on a Kratos AEI MS 50, using conditions identical to those for the low resolution spectra; all peaks in the spectra of compounds (1 equiv. ), then CD,I (excess) added field free region) were detected for compounds 2, [4][5][6] slowly over c. 15 min. The reaction mixture was stirred and 9-12 using either the AEIMS 12 or AEIMS 50 for 2 h, water added, and the product extracted with instruments, and are indicated in the schemes.…”
Section: Methodsmentioning
confidence: 99%
“…Roedel et al reported and we also confirmed that HDMF was formed from the reaction of a-KBA with acetaldehyde. 3 ) From these results, it was concluded that HDMF was formed by the condensation of u-KBA with acetaldehyde which were produced by acid-degradation of threonine. This conclusion may also be supported by the fact that the threonine content of aged sake is about 40 % of that of fresh sake.…”
Section: Determination Of the Odor Unit For Hdmf And Distribution In mentioning
confidence: 97%
“…The three fractions (R, A and N) isolated from fresh sake with ion exchange resins were combined by the method of 2 3 factorial. Table I.…”
Section: The Precursors Of Bfementioning
confidence: 99%